The Relationship between Nutritional Status and Primary Dysmenorrhea Incidence Among Adolescent Girls - Nevi Susianty; Sarah Fitria (Postgraduate, University of Mataram, 2026)
This study aimed to determine the association between nutritional status based on Body Mass Index (BMI) and the occurrence of primary dysmenorrhea among female students at SMAN 07 Pekanbaru. A quantitative analytic study with a cross-sectional design was conducted involving 127 respondents selected from the target population. Primary dysmenorrhea status was assessed using a structured questionnaire, while nutritional status was classified using BMI categories. The results showed that the prevalence of primary dysmenorrhea was high, affecting 79.50% (101 respondents) of the participants. Statistical analysis using the chi-square test indicated that BMI-based nutritional status was not significantly associated with primary dysmenorrhea (p = 0.844). Risk analysis also supported this finding, showing no meaningful evidence of association (OR = 0.72; 95% CI: 0.30–1.71). These findings suggest that primary dysmenorrhea in adolescent girls is likely influenced by multifactorial determinants beyond nutritional status, including hereditary factors, hormonal balance, physical activity, lifestyle habits, and psychological conditions. Preventive and management efforts should therefore incorporate reproductive health education, healthy lifestyle promotion, and broader risk factor control.